Drying of stingless bees pot-pollen using swirling fluidized bed dryer - Luqman Abdul, Halim; Firdaus, Basrawi; Ahmmad Shukrie, Md Yudin; Amir, Abdul Razak; Nor Azfa, Johari; Azira, Muhamad; Mohd Razif, Mamat (Taylor & Francis, 2020)
High moisture content in stingless bees pot-pollen makes preservation difficult. Since potpollen is heat sensitive, using conventional drying techniques below 40-C is time consuming. A fluidized bed dryer (FBD) with swirling distributor is proposed for rapid drying of the pot-pollen while conserving the nutrients. The objectives of this study are to investigate the possibility of using swirling FBD to dry pot-pollen, and to investigate the effect of distributor type and superficial air velocity on pot-pollen drying. Stingless bees pot-pollen from the state of Pahang, Malaysia was dried at different conditions. Three distributor types: perforated, 45- inclination angle, and 67- inclination angle were tested at three superficial air velocities of 1.0 m/s, 1.5 m/s, and 2.0 m/s. Then, moisture content before and after drying were studied. To ensure swirling FBD would preserve the nutrition content of pot-pollen, nuclear magnetic resonance (NMR) analysis on the pot-pollen before and after drying was also carried out. It was found that at higher velocity, the drying rate increased. The 67- swirling distributor has the best drying performance, followed by the 45- swirling and perforated distributor. The highest reduction in moisture content, 13.5% in this study was found when using 67- distributor at 2.0 m/s. This translates to a drying rate of 0.450%/min, about 6.2 times faster than conventional FBD, 5.6 times faster drying rate compared to hot air dryer (HAD) at 45 -C, 44.5 times higher than oven drying at 30 -C, and also a staggering 225 times quicker than cyclic convective dryer (CCD). It is also comparable to lower power levels of microwave assisted vacuum dryer (MW-VD), without damaging pot-pollen nutrients. The NMR analysis showed no adverse effect due to drying. Hence, it is possible to dry pot-pollen rapidly using swirling FBD without damaging its nutrition content, and using the 67- swirling distributor is preferred.